A method for preparing a high-salt wastewater purification material
By introducing carbon -containing ammonium -based ammonium salt intermediates in polyamide materials to form high -salt wastewater purification materials, the problem of sensitivity to chloride in water treatment in water treatment is solved, and the high -salt cutting rate and strong retention rate and strongness are achieved. Anti -pollution ability.
Patent Information
- Application Number
- CN202410615572.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-17
AI Technical Summary
Existing polyamide materials are sensitive to chlorine during water treatment. Long-term contact will lead to oxidation and degradation of the material, degradation of performance, and it is difficult to effectively prevent the penetration of pollutants.
Through acid chlorination, amidation, quaternization and reduction reactions, the carbon nanotube-containing amino quaternary ammonium salt intermediate is prepared, and the condensation reaction is performed with the acid chloride polyamide material to form a high-salt wastewater purification material. This material has more branched chain structures and quaternary ammonium cations, which can improve salt interception rate and anti-pollution ability.
It improves the salt interception rate and anti-pollution ability of wastewater purification materials, enhances the interception ability of larger particles and pollutants, reduces the zeta potential of the material, improves the interception rate of magnesium ions, and improves the material's flux recovery rate.
Smart Images

Figure CN118480264B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater purification materials, in particular to a method for preparing a high-salt wastewater purification material. Background Art
[0002] Polyamide materials have the properties of high efficiency, low energy consumption, high selectivity, and high temperature resistance. They are now widely used in the field of water treatment. However, in the actual water treatment operation process, pollution is inevitable. Polyamide materials are highly sensitive to chlorine, and long-term contact will cause oxidative degradation of the material, resulting in a decrease in the performance of the material. Therefore, it is of great significance to develop polyamide materials with anti-pollution properties. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the deficiencies of the prior art, the present invention provides a method for preparing a high-salt wastewater purification material. The prepared high-salt wastewater purification material has good anti-pollution performance and salt retention rate.
[0005] (II) Technical solution
[0006] A method for preparing a high-salt wastewater purification material, the preparation method is as follows:
[0007] (1) Using deionized water to clean the polysulfone ultrafiltration membrane, pouring a 0.5-1% piperazine aqueous solution on the membrane surface, contacting for 2-5 minutes, pouring out the waste liquid, absorbing the surface water with filter paper, and then pouring a 0.1-0.2% trimesoyl chloride n-hexane solution therein, allowing the interfacial polymerization reaction to proceed for 20-60 seconds, removing the solution, drying, washing with deionized water, and drying to obtain a chlorinated polyamide material.
[0008] (2) Add the acidified carbon nanotubes to N,N-dimethylformamide solvent, then add thionyl chloride thereto, mix well, raise the temperature to 65-85° C., stir and react for 18-30 hours, filter after the reaction, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0009] (3) The acyl chloride carbon nanotubes and tris(2-aminoethyl)amine are mixed uniformly, the temperature is raised to 90-110° C., and the mixture is stirred for reaction for 40-60 hours. After the reaction is completed, the mixture is washed with ethanol and dried to obtain an intermediate 1.
[0010] (4) Under nitrogen conditions, intermediate 1 is added to isopropanol solvent, and then 6-chlorohexanenitrile aqueous solution is added thereto, the temperature is raised to 70-90° C., and the reaction is carried out for 12-24 hours. After the reaction is completed, the mixture is cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0011] (5) Add intermediate 2 to 85-95% ethanol solvent, stir and disperse, add Raney nickel catalyst and potassium hydroxide co-catalyst under hydrogen condition, react at 70-90° C., control the pressure to 1-3 MPa, react for 40-80 min, filter after the reaction, wash with deionized water, and dry to obtain amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0012] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 0.1-1% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 20-60 minutes, pour it out, absorb it with filter paper, and heat and cure it in an oven at 60-80° C. for 4-10 minutes to obtain a high-salt wastewater purification material.
[0013] Preferably, in step (2), the usage ratio of the acidified carbon nanotubes to the thionyl chloride is 1 g:(50-80) mL.
[0014] Preferably, in step (3), the ratio of the amount of acyl chloride carbon nanotubes to tris(2-aminoethyl)amine is 1 g:(200-300) mL.
[0015] Preferably, in step (4), the usage ratio of the intermediate 1, 6-chlorohexanenitrile is 1g:(15-40)g.
[0016] Preferably, in step (5), the usage ratio of intermediate 2, Raney nickel and potassium hydroxide is 1 g:(0.05-0.1) g:(0.0005-0.005) g.
[0017] (III) Beneficial technical effects
[0018] The invention uses acidified carbon nanotubes, tris(2-aminoethyl)amine, 6-chlorohexanenitrile, Raney nickel and the like as raw materials, and prepares an amino quaternary ammonium salt intermediate containing carbon nanotubes through acyl chlorination, amidation, quaternization and reduction reaction. The amino group contained in the intermediate and the acyl chloride group contained in the acyl chlorinated polyamide material are used for condensation reaction to obtain a high-salt wastewater purification material.
[0019] The wastewater purification material prepared by the present invention has a relatively large number of branched chain structures, which can prevent particles with larger sizes from passing through the wastewater purification material, so that the wastewater purification material has a relatively high interception rate, thereby having a relatively good wastewater purification effect. In addition, due to the introduction of the carbon nanotube-containing amino quaternary ammonium salt intermediate, the thickness of the functional layer of the wastewater purification material is increased, and the salt interception rate of the wastewater purification material is further increased. In addition, due to the presence of quaternary ammonium cations, carboxyl groups and other cations, the Zeta potential of the wastewater purification material can be reduced, and the positive charge carried by the wastewater purification material can further increase the interception rate of magnesium ions due to the Donan effect.
[0020] The wastewater purification material prepared by the present invention contains groups such as quaternary ammonium salt groups and hydroxyl groups, and the quaternary ammonium salt groups and hydroxyl groups have strong hydrophilicity, can form a hydration layer with water molecules, prevent pollutants from adhering to the material surface, improve the anti-adhesion property of pollutants to the material, and the quaternary ammonium cation can cause organic anion pollutants to flocculate on the material surface through bridging adsorption, effectively prevent pollutants from being closely combined on the material surface, and therefore have good anti-pollution ability, and the material can be easily removed from the material surface by washing with deionized water, and has a good high flux recovery rate. The wastewater purification material prepared by the present invention has good anti-pollution ability and salt retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The invention is a preparation route of amino quaternary ammonium salt intermediate containing carbon nanotubes. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0023] 1 g of carbon nanotubes was dispersed in a mixed solution of 60 mL of concentrated sulfuric acid and 20 mL of concentrated nitric acid, ultrasonicated at 50° C. for 2 h, washed with deionized water, and dried to obtain acidified carbon nanotubes.
[0024] Example 1
[0025] (1) The polysulfone ultrafiltration membrane is cleaned with deionized water, and a 0.5% piperazine aqueous solution is poured on the membrane surface for 5 minutes, and the waste liquid is poured out, and the surface water is absorbed by filter paper, and then a 0.1% trimesoyl chloride n-hexane solution is poured into it, and the interfacial polymerization reaction is carried out for 50 seconds, and the solution is removed, and the membrane is dried, washed with deionized water, and dried to obtain a chlorinated polyamide material.
[0026] (2) Add 1 g of acidified carbon nanotubes to N,N-dimethylformamide solvent, then add 60 mL of thionyl chloride, mix well, heat to 70° C., stir and react for 24 h. After the reaction is completed, filter, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0027] (3) 0.5 g of acyl chloride carbon nanotubes and 120 mL of tris(2-aminoethyl)amine were mixed evenly, heated to 110° C., and stirred for reaction for 60 h. After the reaction was completed, the mixture was washed with ethanol and dried to obtain intermediate 1.
[0028] (4) Under nitrogen conditions, 2 g of intermediate 1 was added to isopropanol solvent, and then 80 g of 6-chlorohexanenitrile aqueous solution was added thereto, the temperature was raised to 80° C., and the reaction was carried out for 24 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0029] (5) 10 g of intermediate 2 was added to 90% ethanol solvent, stirred and dispersed, and 0.6 g of Raney nickel catalyst and 0.05 g of potassium hydroxide co-catalyst were added thereto under hydrogen conditions. The reaction was carried out at 90° C. and the pressure was controlled to be 1.5 MPa for 60 min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0030] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 0.1% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 60 minutes, pour it out, absorb it with filter paper, and heat and cure it in an oven at 80° C. for 4 minutes to obtain a high-salt wastewater purification material.
[0031] Example 2
[0032] (1) The polysulfone ultrafiltration membrane is cleaned with deionized water, and a 0.6% piperazine aqueous solution is poured on the membrane surface for 4 minutes, and the waste liquid is poured out, and the surface water is absorbed by filter paper, and then a 0.2% trimesoyl chloride n-hexane solution is poured into it, and the interfacial polymerization reaction is carried out for 60 seconds, and the solution is removed, and the membrane is dried, washed with deionized water, and dried to obtain a chlorinated polyamide material.
[0033] (2) Add 1 g of acidified carbon nanotubes to N,N-dimethylformamide solvent, then add 80 mL of thionyl chloride, mix well, heat to 85° C., stir and react for 30 h. After the reaction is completed, filter, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0034] (3) 0.5 g of acyl chloride carbon nanotubes and 150 mL of tris(2-aminoethyl)amine were mixed evenly, heated to 100° C., and stirred for reaction for 40 h. After the reaction was completed, the mixture was washed with ethanol and dried to obtain intermediate 1.
[0035] (4) Under nitrogen conditions, 2 g of intermediate 1 was added to isopropanol solvent, and then 30 g of 6-chlorohexanenitrile aqueous solution was added thereto, the temperature was raised to 75° C., and the reaction was carried out for 18 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0036] (5) 10 g of intermediate 2 was added to 95% ethanol solvent, stirred and dispersed, and 1 g of Raney nickel catalyst and 0.005 g of potassium hydroxide co-catalyst were added thereto under hydrogen conditions. The reaction was carried out at 80° C. and the pressure was controlled to be 3 MPa for 80 min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0037] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 0.3% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 50 minutes, pour it out, dry it with filter paper, and heat and cure it in an oven at 70° C. for 10 minutes to obtain a high-salt wastewater purification material.
[0038] Example 3
[0039] (1) The polysulfone ultrafiltration membrane is cleaned with deionized water, and a 0.8% piperazine aqueous solution is poured on the membrane surface for 4 minutes, the waste liquid is poured out, the surface water is absorbed by filter paper, and then a 0.15% trimesoyl chloride n-hexane solution is poured into it, and the interfacial polymerization reaction is carried out for 20 seconds, the solution is removed, the membrane is dried, the membrane is washed with deionized water, and the membrane is dried to obtain a chlorinated polyamide material.
[0040] (2) Add 1 g of acidified carbon nanotubes to N,N-dimethylformamide solvent, then add 60 mL of thionyl chloride, mix well, heat to 65° C., stir and react for 18 h. After the reaction is completed, filter, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0041] (3) 0.5 g of acyl chloride carbon nanotubes and 100 mL of tris(2-aminoethyl)amine were mixed evenly, heated to 901° C., and stirred for reaction for 48 h. After the reaction was completed, the mixture was washed with ethanol and dried to obtain intermediate 1.
[0042] (4) Under nitrogen conditions, 2 g of intermediate 1 was added to isopropanol solvent, and then 40 g of 6-chlorohexanenitrile aqueous solution was added thereto, the temperature was raised to 70° C., and the reaction was carried out for 12 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0043] (5) 10 g of intermediate 2 was added to 85% ethanol solvent, stirred and dispersed, and 0.5 g of Raney nickel catalyst and 0.01 g of potassium hydroxide co-catalyst were added thereto under hydrogen conditions. The reaction was carried out at 70° C. and the pressure was controlled to be 1 MPa for 40 min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0044] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 0.5% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 20 minutes, pour it out, dry it with filter paper, and heat and cure it in an oven at 60° C. for 6 minutes to obtain a high-salt wastewater purification material.
[0045] Example 4
[0046] (1) The polysulfone ultrafiltration membrane is cleaned with deionized water, and a 1% piperazine aqueous solution is poured on the membrane surface for 2 minutes, the waste liquid is poured out, the surface water is absorbed by filter paper, and then a 0.16% trimesoyl chloride n-hexane solution is poured into it, and the interfacial polymerization reaction is carried out for 60 seconds, the solution is removed, the membrane is dried, the membrane is washed with deionized water, and the membrane is dried to obtain a chlorinated polyamide material.
[0047] (2) Add 1 g of acidified carbon nanotubes to N,N-dimethylformamide solvent, then add 50 mL of thionyl chloride, mix well, heat to 85° C., stir and react for 30 h. After the reaction is completed, filter, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0048] (3) 0.5 g of acyl chloride carbon nanotubes and 140 mL of tris(2-aminoethyl)amine were mixed evenly, heated to 100° C., and stirred for reaction for 52 h. After the reaction was completed, the mixture was washed with ethanol and dried to obtain intermediate 1.
[0049] (4) Under nitrogen conditions, 2 g of intermediate 1 was added to isopropanol solvent, and then 70 g of 6-chlorohexanenitrile aqueous solution was added thereto, the temperature was raised to 90° C., and the reaction was carried out for 24 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0050] (5) 10 g of intermediate 2 was added to 90% ethanol solvent, stirred and dispersed, and 0.8 g of Raney nickel catalyst and 0.04 g of potassium hydroxide co-catalyst were added thereto under hydrogen conditions. The reaction was carried out at 85° C. and the pressure was controlled to be 2.5 MPa for 80 min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0051] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 0.8% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 40 minutes, pour it out, absorb it with filter paper, and heat and cure it in an oven at 80° C. for 10 minutes to obtain a high-salt wastewater purification material.
[0052] Example 5
[0053] (1) The polysulfone ultrafiltration membrane is cleaned with deionized water, and a 0.9% piperazine aqueous solution is poured on the membrane surface for 5 minutes, and the waste liquid is poured out, and the surface water is absorbed by filter paper, and then a 0.1% trimesoyl chloride n-hexane solution is poured into it, and the interfacial polymerization reaction is carried out for 60 seconds, and the solution is removed, and the membrane is dried, washed with deionized water, and dried to obtain a chlorinated polyamide material.
[0054] (2) Add 1 g of acidified carbon nanotubes to N,N-dimethylformamide solvent, then add 50 mL of thionyl chloride, mix well, heat to 80° C., stir and react for 30 h. After the reaction is completed, filter, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes.
[0055] (3) 0.5 g of acyl chloride carbon nanotubes and 150 mL of tris(2-aminoethyl)amine were mixed evenly, heated to 90° C., and stirred for reaction for 60 h. After the reaction was completed, the mixture was washed with ethanol and dried to obtain intermediate 1.
[0056] (4) Under nitrogen conditions, 2 g of intermediate 1 was added to isopropanol solvent, and then 70 g of 6-chlorohexanenitrile aqueous solution was added thereto, the temperature was raised to 90° C., and the reaction was carried out for 24 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with deionized water, and dried to obtain intermediate 2.
[0057] (5) 10 g of intermediate 2 was added to 80% ethanol solvent, stirred and dispersed, and 1 g of Raney nickel catalyst and 0.05 g of potassium hydroxide co-catalyst were added thereto under hydrogen conditions. The reaction was carried out at 90° C. and the pressure was controlled to be 3 MPa for 80 min. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an amino quaternary ammonium salt intermediate containing carbon nanotubes.
[0058] (6) Add the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, prepare a 1% aqueous solution, stir evenly, and then pour it onto the chlorinated polyamide material, react for 50 minutes, pour it out, dry it with filter paper, and heat and cure it in an oven at 70° C. for 8 minutes to obtain a high-salt wastewater purification material.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that step (6) does not contain the carbon nanotube-containing amino quaternary ammonium salt intermediate.
[0061] Anti-pollution ability test: Use deionized water to test the flux at 0.5MPa. After the water flux of the material is stable, record the water flux J. 1 , 1g / L humic acid and sodium alginate were used as pollution reagents, the water flux was measured every 1h, the feed liquid containing pollutants was emptied, the material was washed with deionized water, and the pure water flux was tested again, and the water flux J was recorded.2 . Flux recovery rate (%) = J 2 / J 1 .
[0062] Humic acid flux recovery rate (%) Sodium alginate flux recovery rate (%) Example 1 96.4 95.8 Example 2 96.8 96.3 Example 3 97.5 98.6 Example 4 98.8 98.9 Example 5 99.3 99.2 Comparative Example 1 73.4 74.0
[0063] The greater the flux recovery rate, the stronger the anti-pollution ability. It can be seen from the table that the high-salt wastewater purification material prepared by the present invention has good anti-pollution ability.
[0064] Salt retention rate test: At room temperature, use 1g / L magnesium sulfate solution as the feed liquid to test the salt retention rate of the material. Pre-press the high-salt wastewater purification material at 0.5MPa for 1h, and use a conductivity tester to measure the inorganic salt conductivity of the raw liquid and the permeate at 0.5MPa. Salt retention rate (%) = 1-(C P / C T ), C T is the conductivity of inorganic salt in raw material solution, μS / cm, C P is the inorganic salt conductivity of the permeate, μS / cm.
[0065]
[0066]
[0067] It can be seen from the table that the material prepared by the present invention has a good salt retention rate and thus has a good purification effect.
[0068] The applicant declares that the present invention illustrates the high-salt wastewater purification material and the preparation method thereof through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a material for purifying high-salinity wastewater, characterized in that: The preparation method is as follows: (1) using deionized water to clean the polysulfone ultrafiltration membrane, pouring a 0.5-1% piperazine aqueous solution on the membrane surface, contacting for 2-5 minutes, pouring out the waste liquid, absorbing the surface water with filter paper, and then pouring a 0.1-0.2% trimesoyl chloride n-hexane solution into it, allowing the interfacial polymerization reaction to proceed for 20-60 seconds, removing the solution, drying, washing with deionized water, and drying to obtain a chlorinated polyamide material; (2) adding the carbon nanotube-containing amino quaternary ammonium salt intermediate to deionized water to prepare a solution, stirring evenly, and then pouring it onto the chlorinated polyamide material, reacting for 20-60 minutes, pouring it out, drying it with filter paper, and heating and curing it in an oven at 60-80° C. for 4-10 minutes to obtain a high-salt wastewater purification material. The preparation method of the carbon nanotube-containing amino quaternary ammonium salt intermediate is: S1, adding the acidified carbon nanotubes to N,N-dimethylformamide solvent, then adding thionyl chloride thereto, mixing evenly, heating to 65-85° C., stirring and reacting for 18-30 hours, filtering after the reaction, washing with tetrahydrofuran, and drying to obtain acyl chloride carbon nanotubes; S2, mixing the acyl chloride carbon nanotubes and tris(2-aminoethyl)amine evenly, heating to 90-110° C., stirring and reacting for 40-60 hours, and after the reaction, washing with ethanol and drying to obtain intermediate 1; S3, under nitrogen conditions, adding intermediate 1 to isopropanol solvent, then adding 6-chlorohexanenitrile aqueous solution thereto, heating to 70-90°C, reacting for 12-24h, after the reaction is completed, cooling to room temperature, rotary evaporation, washing with deionized water, and drying to obtain intermediate 2; S4. Add intermediate 2 to 85-95% ethanol solvent, stir and disperse, add Raney nickel catalyst and potassium hydroxide co-catalyst thereto under hydrogen condition, control the pressure at 70-90° C. to be 1-3 MPa, react for 40-80 min, filter after the reaction, wash with deionized water, and dry to obtain amino quaternary ammonium salt intermediate containing carbon nanotubes.
2. The method for preparing a high-salinity wastewater purification material according to claim 1, characterized in that: In the step (2), the concentration of the solution is 0.1-1%.
3. The method for preparing the high-salinity wastewater purification material according to claim 1, characterized in that: In the step S1, the usage ratio of the acidified carbon nanotubes and thionyl chloride is 1 g: (50-80) mL.
4. The method for preparing a high-salinity wastewater purification material according to claim 1, characterized in that: In the step S2, the ratio of the amount of the chlorinated carbon nanotubes to the amount of tris(2-aminoethyl)amine is 1 g:(200-300) mL.
5. The method for preparing a high-salinity wastewater purification material according to claim 1, characterized in that: In the step S3, the usage ratio of the intermediate 1 and 6-chlorohexanenitrile is 1 g:(15-40) g.
6. The method for preparing a high-salinity wastewater purification material according to claim 1, characterized in that: In the step S4, the usage ratio of the intermediate 2, Raney nickel and potassium hydroxide is 1 g:(0.05-0.1) g:(0.0005-0.005) g.
Citation Information
Patent Citations
Preparation method of in-situ quaternized antibacterial agent on surface of carbon nano tube
CN106118198A
Amino-functionalized single-walled carbon nanotube modified polyamide nanofiltration membrane as well as preparation method and application thereof
CN113117525A